Effects of leg massage on recovery from high intensity cycling exercise - Robertson, A.; Watt, J. M.; Galloway, S. D. R. (British Journal of Sports Medicine, 2004)
Background: The effect of massage on recovery from high intensity exercise is debatable. Many studies on massage suffer from methodological flaws such as poor standardisation of previous exercise, lack of dietary control, and inappropriate massage duration.